Relation between Total Quality Management Practices and Business Excellence: Evidence from Private Service Firms in Jordan - Samawi, Ghazi A.; Abu-Tayeh, Bandar K; Yosef, Fathi; Madanat, Metri; Al-Qatawneh, Manar I. (International Review of Management and Marketing, 2018)
This study examines the extent of total quality management (TQM) practices implemented by private service firms and their impact on organisational excellence. Its importance derives from the major contribution of the private sector to the economy. TQM practices concerning leadership, human resource focus, process management, customer focus, and information and analysis found to have a positive effect on organisational excellence in the firms surveyed. This is the first study to examine the case of private sector firms offering specialized services, focusing on the KAAEPS. It will thus provide a model for private firms to improve their performance and motivate them to adopt TQM practices. It also provides a conceptual model for use by other researchers. Keywords: TQM practices, excellence, private service firms, King Abdullah II Award for Excellence, competitiveness. JEL Classification: Z00